The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/opth.s136061
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of moderate-to-high hyperopia with the WaveLight Allegretto 400 and EX500 excimer laser systems

Abstract: PurposeTo evaluate the efficacy of treating patients with +3.00 diopters (D) to +6.00 D of hyperopia via laser-assisted in situ keratomileusis (LASIK) with the WaveLight Allegretto 400 and EX500 excimer laser systems.SettingPrivate clinical ophthalmology practice.Patients and methodsThis was a retrospective study of patients undergoing LASIK treatments of +3.00 to +6.00 D on two different WaveLight laser systems: 163 eyes on the 400 (Hertz) Hz system and 54 eyes on the 500 Hz system. The duration of follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
(18 reference statements)
1
14
0
Order By: Relevance
“…Treatment of hyperopia with incorporation of HOA removal via topographic-guided ablation has enormous potential. Making a more uniform cornea may well increase overall visual stability, and when combined with the already noted accuracy and stability in our published hyperopia paper, 5 may make hyperopic excimer laser treatment more widespread and trusted among refractive surgeons. We already have seen an increase in quantity and quality of vision documented in the LYRA Protocol manuscripts, 2 4 and further refinement of the nomograms may make this procedure more accurate.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Treatment of hyperopia with incorporation of HOA removal via topographic-guided ablation has enormous potential. Making a more uniform cornea may well increase overall visual stability, and when combined with the already noted accuracy and stability in our published hyperopia paper, 5 may make hyperopic excimer laser treatment more widespread and trusted among refractive surgeons. We already have seen an increase in quantity and quality of vision documented in the LYRA Protocol manuscripts, 2 4 and further refinement of the nomograms may make this procedure more accurate.…”
Section: Discussionmentioning
confidence: 55%
“…The author undertook a retrospective study and published the results of patients from +3.0 D to +6.0 D of hyperopic correction treated with both the WaveLight ® EX500 and Allegretto 400. 5 That study demonstrated a far lower regression rate compared with past studies on treatment of lower amounts of hyperopia. Many practices report only 10% of their treatments are hyperopic, in our practice, it is about 30%.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although some excimer lasers have been approved for corrections up to +6.0 D ( 1 , 7 ) and current technology using models with wide ablation and high correction speed has greatly improved prognosis ( 1 , 8 ) [large diameter optical areas being more resistant to epithelial hyperplasia that is responsible for real regression ( 1 , 7 )], latent hyperopia is often the reason why refractive surgeons avoid approaching cases of hyperopia and hyperopic astigmatism or limit the surgeries to refractive errors below +3.0 D ( 1 , 8 ). Laser refractive treatment is difficult to choose because ablation of manifest refraction in hyperopia or hyperopic astigmatism may lead postoperatively to recurrence of a degree of hyperopia, falsely interpreted as regression of the laser procedure ( 1 , 6 , 7 ), while ablation of cycloplegic refraction may lead to myopic refraction in the immediate postoperative period, causing an unsatisfactory UDVA ( 1 ). In order to compensate in part for the latent hyperopia, Kanellopoulos proposed a nomogram that involves full treatment in the case of the cylinder and the ablation of the manifest refraction sphere with an addition of +0.25 D for the dominant eye and up to +0.75 D for the non-dominant eye ( 1 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 As spherical aberration was reduced via several laser modalities, such as wavefront guided, wavefront optimized (WFO), and aspheric ablation, outcomes improved dramatically, 3 but the prejudice among surgeons on performing high myopic excimer laser corrections such as −9.00 D and higher remained. 4 …”
Section: Introductionmentioning
confidence: 99%